Manajemen Perubahan Lembaga Pendidikan Pada Madrasah Ibtidaiyah Negeri 1 Balikpapan - Hamid, Abdul; Muadin, Ahmad (El-Idare, 2024)
This study investigates effective change management strategies to enhance the quality of education at Madrasah Ibtidaiyah Negeri 1 Balikpapan. Through a qualitative approach and descriptive analysis, the study explores the necessary steps in designing, implementing, and evaluating changes within the educational institution context. The research findings indicate that the implementation of appropriate change management strategies, such as strengthening leadership, empowering educators, developing relevant curricula, optimizing resources, and actively engaging various stakeholders, significantly contributes to improving the quality of education. Strong leadership, educator empowerment through training and collaboration, and the development of student-focused curricula emerge as key factors in achieving change goals. Furthermore, resource optimization and active involvement of parents, school committees, and the community are also crucial in creating conducive learning environments and supporting the change process. By comprehensively and sustainably applying these strategies, Madrasah Ibtidaiyah Negeri 1 Balikpapan has the potential to continuously enhance the quality of education and better prepare students to face future challenges. This study contributes to understanding the importance of change management in the educational context and provides practical guidance for educational institutions in navigating ongoing change dynamics.